2011
DOI: 10.2147/tcrm.s10145
|View full text |Cite
|
Sign up to set email alerts
|

The lupus band test in systemic lupus erythematosus patients

Abstract: The lupus band test (LBT) is a diagnostic procedure that is used to detect deposits of immunoglobulins and complement components along the dermoepidermal junction in patients with lupus erythematosus (LE). The LBT is positive in about 70%–80% of sun-exposed non-lesional skin specimens obtained from patients with systemic LE (SLE), and in about 55% of SLE cases if sun-protected nonlesional skin is analyzed. In patients with cutaneous LE only, the lesional skin usually shows a positive LBT. The LBT helps in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 21 publications
2
43
0
6
Order By: Relevance
“…In the present study, the common feature was observed as a continuous fluorescent band with moderate to marked intensity consisting multiple bright dots or clumps, consistent with previous report [4]. For single immunoreactant deposition, the staining pattern varied among individual samples.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the common feature was observed as a continuous fluorescent band with moderate to marked intensity consisting multiple bright dots or clumps, consistent with previous report [4]. For single immunoreactant deposition, the staining pattern varied among individual samples.…”
Section: Discussionsupporting
confidence: 93%
“…The staining pattern of immunoreactants in lesional and non-lesional skin of lupus patients were thoroughly discussed by Reich A et al [4]. In the present study, the common feature was observed as a continuous fluorescent band with moderate to marked intensity consisting multiple bright dots or clumps, consistent with previous report [4].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A skin biopsy revealed leucocytoclastic vasculitis. Immunohistochemistry staining revealed linear deposits of IgG and C3 along the dermoepidermal transition (typical finding in patients with SLE), as well as IgA deposits on superficial dermal capillaries 2. IgA vasculitis was then assumed, without lupus flare or increased SLE activity.…”
Section: Case Presentationmentioning
confidence: 85%
“…1 Lupus band test (LBT) should be considered positive when deposition of IgM in sun-exposed skin forms a continuous band over at least 50% of the width of the biopsy specimen, which shows at least moderate intensity. 2 The pattern of the deposition is typically as granules or closely spaced fibrils. 3 In the previous study, LBT of DLE demonstrated depositions of IgG (58%), IgA (38%), IgM (78%), and C3 (72%).…”
Section: Introductionmentioning
confidence: 99%